a) 2x-7y+3y+4x-7y
b) -2,5a + 3 1/2a^{2}+a-a^{2)-0,5a
c) {1}{2} ab - 3/4a2 + 3 3/4 ab-1,5a2+ 5/8 a2
d) 1,2a- -2/3a2+ 0,75 - 1 3/8a- 1/2 + 2/9a2


Odpowiedź :

Odpowiedź:

a)

2x - 7y + 3y + 4x - 7y = 6x - 11y

b)

-2,5a + 3 1/2a^{2} + a - a^{2) - 0,5a = 2 1/2a² - 2a  

c)

{1}{2} ???

ab - 3/4a² + 3 3/4 ab - 1,5a² + 5/8 a2² = 5/8a^4 - 0,75a² - 1,5a² + 4 3/4ab

d)

1,2a - 2/3a² + 0,75 - 1 3/8a - 1/2 + 2/9a² = -6/9á² + 2/9a² + 1,2a - 1,375a + 0,75  - 0,5 = -4/9a² - 0,175a + 0,25

Szczegółowe wyjaśnienie: